2011
DOI: 10.2174/157016211798038597
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral Therapy in Prevention of HIV and TB: Update on Current Research Efforts

Abstract: There is considerable scientific evidence supporting the use of antiretroviral therapy (ART) in prevention of human immunodeficiency virus (HIV) and tuberculosis (TB) infections. The complex nature of the HIV and TB prevention responses, resource constraints, remaining questions about cost and feasibility, and the need to use a solid evidence base to make policy decisions, and the implementation challenges to translating trial data to operational settings require a well-organised and coordinated response to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 92 publications
(90 citation statements)
references
References 51 publications
0
89
0
1
Order By: Relevance
“…160 HPTN 052, 161,162 conducted in 13 sites in nine countries including India and Thailand, demonstrated that earlier ART reduces the risk of heterosexual HIV transmission by 96% 163 in discordant couples and confirmed results of observational and ecological studies. [164][165][166][167][168][169] These results prompted a retrospective study of treated and untreated discordant couples in China, 170 which showed a relative reduction of 26% of HIV-1-linked transmission (Table 2).…”
Section: Treatment As Prevention (Tasp)mentioning
confidence: 99%
“…160 HPTN 052, 161,162 conducted in 13 sites in nine countries including India and Thailand, demonstrated that earlier ART reduces the risk of heterosexual HIV transmission by 96% 163 in discordant couples and confirmed results of observational and ecological studies. [164][165][166][167][168][169] These results prompted a retrospective study of treated and untreated discordant couples in China, 170 which showed a relative reduction of 26% of HIV-1-linked transmission (Table 2).…”
Section: Treatment As Prevention (Tasp)mentioning
confidence: 99%
“…There are relatively few such studies focussing on Asia. 16,17 The HPTN 074 vanguard study for a network-based randomised HIV prevention trial comparing an integrated intervention including supported ART compared with the standard of care for IDUs may consider sites in Asia.…”
Section: Prevention Benefit Of Art Testing and Treatingmentioning
confidence: 99%
“…84 Eight different trials of ART for HIV prevention that include TB outcomes are currently underway or planned. 85 …”
Section: Participantsmentioning
confidence: 99%